Relatório de estágio curricular supervisionado em medicina veterinária - área de clínica e cirurgia de pequenos animais - Bertti, Hellen (2015)
This report describes the set of clinical and surgical activities monitored by the academic Hellen Bertti, during the Supervised Curricular Internship in Veterinary Medicine (ECSMV) at UNIPAMPA. The academic was guided by professor Dr. Maria Elisa Trost and the activities described here were developed with the Clínica & Estética Empório de Bicho, located in the city of Caxias do Sul, Rio Grande do Sul, from August 3, 2015 to 23 October of the same year, totaling 480 hours, under the supervision of Veterinary Doctor Luciane Ballardin. During this period, 117 clinical and 24 surgical cases were followed, in addition to other procedures performed at the clinic. Following are described in detail relevant clinical and surgical cases monitored during that period by the academic.